1980
DOI: 10.1029/jb085ib06p03209
|View full text |Cite
|
Sign up to set email alerts
|

Iron and titanium distribution on the moon from orbital gamma ray spectrometry with implications for crustal evolutionary models

Abstract: A set of Fe and Ti maps and regional values are obtained from the Apollo 15 and 16 orbital gamma ray data by energy band analysis. High‐Ti basalts predominate the early and late stages of mare volcanism with high‐Fe basaltic volcanism in the interim. The first evidence of a high‐Ti‐KREEP basalt association is found in the Aristarchus region. A N‐S asymmetry for Fe and Ti in the east limb and farside highlands complicates the E‐W asymmetry for Th but substantiates crustal inhomogeneity. The observed crustal inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 8 publications
2
73
0
Order By: Relevance
“…This range contains the average FeO abundance derived from Clementine spectral reflectance data (FeO = 4.2% ] and <4.9% Pieters and Tompkins, 1999]) and from analyses of lunar meteorites (5.2% [Palme et al, 1991]). However, it is significantly less than that derived from Apollo gamma-ray data (FeO = 7.7% [Haines and Metzger, 1980;Davis, 1980]). Our result is consistent with a very high abundance of plagioclase in the highlands, which is predicted by the magma ocean theory of crustal evolution (see, e.g., the review by Warren [1986, and references therein]).…”
Section: Summary and Discussionmentioning
confidence: 92%
“…This range contains the average FeO abundance derived from Clementine spectral reflectance data (FeO = 4.2% ] and <4.9% Pieters and Tompkins, 1999]) and from analyses of lunar meteorites (5.2% [Palme et al, 1991]). However, it is significantly less than that derived from Apollo gamma-ray data (FeO = 7.7% [Haines and Metzger, 1980;Davis, 1980]). Our result is consistent with a very high abundance of plagioclase in the highlands, which is predicted by the magma ocean theory of crustal evolution (see, e.g., the review by Warren [1986, and references therein]).…”
Section: Summary and Discussionmentioning
confidence: 92%
“…The FeO contents determined for locations B, C, and D are very similar, 12-13 wt%, about 1 or 2 wt% higher than at location A. The average Ti02 content ranges from low (-1.2 wt%) at areas A and B to moderate (2.1 wt%) at region D. Spudis and Hawke (1986), using the Apollo gamma-ray data of Davis (1980), reported FeO of 9.5-12.4 wt% and Ti02 of 1.7-2.3 wt% for the Apennine Bench Formation, a composition consistent with that of Apollo 15 KREEP basalts. The Apollo FeO values are in agreement with the Clementine values, though the FeO values for the locations examined with Clementine are mostly at the high end of the Apollo range.…”
Section: Apennine Bench Formationmentioning
confidence: 99%
“…The recent Galileo and Clementine missions allowed us to take a global look at the composition of the Moon. Previous comprehensive mapping efforts have estimated Ti02 (Charette et al, 1974;Head, 1976;Johnson et al, 1977;Head et al, 1978;Pieters, 1978;Davis, 1980;Jaumann, 1991;Johnson et al, 1991;Greeley et al, 1993;Pieters et al, 1993;Melendrez et al, 1994;Campbell et al, 1997), and it has been suggested that relative FeO content can be estimated for a few cases from the depth of the 1 .O p m absorption band (Pieters, 1978). Recently, analytical techniques for the accurate determination of FeO (Lucey et al, 1995) and Ti02 (Lucey et al, 1996(Lucey et al, , 1998Blewett et al, 1997) abundances of lunar surface units from Clementine and Galileo spectral reflectance data have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Head (1 976) produced a generalized color difference map of the nearside lunar maria that showed intermediate values between the blue and red end members. The "Charette relation" was later used and improved upon by others, first by Johnson et al (1977) and later by Pieters (1978) (Metzer and Parker, 1979;Davis, 1980), Earth-based spectral reflectance (Jaumann, 1991;Melendrez et al, 1994), and Earthbased radar (Campbell et al, 1997). The Ti02 measurement techniques that utilize the Charette relation are limited to mature mare surfaces.…”
Section: Introductionmentioning
confidence: 99%